Development, Democracy and the State : Critiquing the Kerala Model of Development. - Raman, K. Ravi (Routledge contemporary South Asia series., 2010)
A comprehensive analysis of the Kerala Model of Social Development to date. Using an interdisciplinary approach, it sheds light on the paradoxes of the Indian state and critiques its model of economic development.